Holocene vegetation and palaeoenvironments of the Southern Cederberg mountains of South Africa : palynological evidence from fossil hyrax (Procavia) dung middens - Seliane, Mamoluoane (Department of Environmental and Geographical Science, 2014)
Includes bibliographical references (leaves 114-121).